Strategies for specific multimodal imaging of cancer-associated fibroblasts and applications in theranostics of cancer - Li Wen; Chengxue He; Yanhui Guo; Nina Zhou; Xiangxi Meng; Yuwen Chen; Cheng Ma; Hua Zhu; Zhi Yang; Lei Xia (Materials Today Bio)
Fibroblast activating protein (FAP) is up-regulated in cancer-associated fibroblasts (CAFs) of more than 90 % of tumor microenvironment and also highly expressed on the surface of multiple tumor cells like glioblastoma, which can be used as a specific target for tumor diagnosis and treatment. At present, small-molecule radiotracer targeting FAP with high specificity exhibit limited functionality, which hinders the integration of theranostics as well as multifunctionality. In this work, we have engineered a multifunctional nanoplatform utilizing organic melanin nanoparticles that specifically targets FAP, facilitating both multimodal imaging and synergistic therapeutic applications. This nanoplatform can perform positron emission tomography (PET), magnetic resonance imaging (MRI) and photoacoustic imaging (PAI) with strong near infrared absorption and metal chelating ability, achieving efficiently targeting accumulation and display long retention in the tumor region. Meanwhile, 131I-labeled nanoplatform for targeted radioisotope therapy (TRT) and photothermal therapy (PTT) were significantly suppressed tumor growth in glioblastoma xenograft models without obvious side effects. These results demonstrated that this novel nanoparticles-based theranostics nanoplatform can effectively enhance multimodal imaging and targeted radionuclide-photothermal synergistic therapy for solid tumors with FAP expression.